2004
DOI: 10.1111/j.1537-2995.2003.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival after transfusion as assessed in a large multistate US cohort

Abstract: These data from the mid 1990s can be used in models of the effectiveness of risk reduction interventions and in models of the disease consequences of infections transmitted through blood transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
44
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 14 publications
(27 reference statements)
8
44
1
Order By: Relevance
“…Relatively few pediatric patients were included in the studies on which these probabilities were determined and none specifically analyzed data and factors associated with survival in children. Six of the studies reported survival rates after transfusion with population‐based data 2,3,5‐8 . Whyte 3 reported PTSR for all patients transfused over a 40‐day period in Canterbury, New Zealand, in 1984; there were 38 patients 19 years of age or younger of whom 35 of 38 (92%) were alive at 24 months after transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatively few pediatric patients were included in the studies on which these probabilities were determined and none specifically analyzed data and factors associated with survival in children. Six of the studies reported survival rates after transfusion with population‐based data 2,3,5‐8 . Whyte 3 reported PTSR for all patients transfused over a 40‐day period in Canterbury, New Zealand, in 1984; there were 38 patients 19 years of age or younger of whom 35 of 38 (92%) were alive at 24 months after transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Of the six population‐based studies, this latter is the most informative with respect to PTSR in pediatric patients. No further analysis specific to pediatric patients was performed; however, Kleinman and coworkers 7 with a managed care administrative claims database covering 20 states identified 6960 patients who received transfusions in 1995 of which 6779 were included in their study. Their results show a PTSR of 69 percent at 1 year, 60 percent at 2 years, and 46 percent at 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This does not reflect the pattern of HCV acquisition in the UK, where most infections are acquired via injecting drug use [3]. As transfusion recipients are more likely to have co-morbidity [30, 31] and patients with a history of injecting drug use are likely to differ in other important ways, including alcohol use, this may limit general application of the findings [30, 31]. …”
Section: Discussionmentioning
confidence: 99%
“…Historical perspectives are useful in providing context in caring for patients, which is why long‐term follow‐up studies are so valuable 2,3 . The patient profiles of transfused pediatric patients have not changed dramatically.…”
mentioning
confidence: 99%